Literasi Keuangan Digital dan Kepercayaan Keuangan memengaruhi Kepercayaan Keuangan serta Implikasinya terhadap Kesejahteraan Keuangan pada Generasi Z di Yogyakarta - Nurafina, Aulia; Sari, Pristin Prima; Maulida , Alfiatul (Indonesian Journal Publisher, 2025)
The development of financial technology in Indonesia is currently accelerating, providing economic changes and utilizing technology for various conveniences related to the finances of each individual. This is a challenge and requires us to be able to have the appropriate knowledge and skills in using financial technology correctly, appropriately and safely to avoid mistakes in financial matters. This study aims to analyze digital financial literacy and financial trust that affect financial behavior and its implications for financial well-being in Generation Z. This study uses a quantitative method with a sample of 150 respondents who are Generation Z domiciled in the Special Region of Yogyakarta. The sampling technique is by distributing data in the form of questionnaires and sample sizes using hair et.al because the population is not yet known apsti. The measuring tools used are validity tests and reliability tests as well as data analysis techniques using path analysis with the help of SmarPLS software analysis version 3.0. The results of the research analysis prove that the hypothesis is accepted, namely digital financial literacy and financial trust affect financial behavior, as well as financial trust and financial behavior affect financial well-being. This shows that these three variables have a positive impact on financial well-being which plays a significant role in Generation Z in the Special Region of Yogyakarta.